2018
DOI: 10.1371/journal.pone.0193279
|View full text |Cite|
|
Sign up to set email alerts
|

HMP-1/α-catenin promotes junctional mechanical integrity during morphogenesis

Abstract: Adherens junctions (AJs) are key structures regulating tissue integrity and maintaining adhesion between cells. During morphogenesis, junctional proteins cooperate closely with the actomyosin network to drive cell movement and shape changes. How the junctions integrate the mechanical forces in space and in time during an in vivo morphogenetic event is still largely unknown, due to a lack of quantitative data. To address this issue, we inserted a functional Fluorescence Resonance Energy Transfer (FRET)-based fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Thus, while the cells are restructuring their apical junctions, the basolateral membranes are relieving the tension generated in CeAJs through protrusive activity [85]. In accordance, a FRET-based force sensor placed in the HMP-1 gene, revealed that the tension exerted at the CeAJs decrease by 1.3-to 1.5-fold even though cells are experiencing high actomyosin contraction, supporting the idea that membrane protrusion acts as a tension relieving mechanism [54,[84][85][86]. Adding to tension-relieving mechanisms, junction strengthening also provides a means by which cells can reinforce tension resistance.…”
Section: St Stage Of Elongationmentioning
confidence: 62%
See 2 more Smart Citations
“…Thus, while the cells are restructuring their apical junctions, the basolateral membranes are relieving the tension generated in CeAJs through protrusive activity [85]. In accordance, a FRET-based force sensor placed in the HMP-1 gene, revealed that the tension exerted at the CeAJs decrease by 1.3-to 1.5-fold even though cells are experiencing high actomyosin contraction, supporting the idea that membrane protrusion acts as a tension relieving mechanism [54,[84][85][86]. Adding to tension-relieving mechanisms, junction strengthening also provides a means by which cells can reinforce tension resistance.…”
Section: St Stage Of Elongationmentioning
confidence: 62%
“…Consequently, cell-cell adhesion is unbalanced by an unequal distribution of pulling forces. This lowers resistance to tension, resulting in rupture and aborted elongation [15,16,84]. In the same line, Martin and colleagues propose that differential employment of actomyosin regulatory pathways by the epidermal subtypes may simultaneously relieve tension.…”
Section: St Stage Of Elongationmentioning
confidence: 96%
See 1 more Smart Citation
“…Biosensor imaging has been applied to classic models of embryonic development less frequently than whole animal physiology, with only a handful of successes reported in zebrafish (Andrews et al, 2016; Muto et al, 2011; Xu et al, 2012; Zhao et al, 2015), Drosophila (Markova et al, 2015), and C. elegans (Kelley et al, 2015; Vuong-Brender et al, 2018). Consequently, less is known about protein activities during development outside of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…HMP-1/-catenin is a component of the cadherin-catenin complex that protects epidermal adherens junctions from contractile stresses imposed by circumferential actomyosin bundles during embryonic morphogenesis (Vuong-Brender et al 2018). UNC-94 is localized to the adherens junction in proximity to, but not directly interacting with, HMP-1 (Cox-Paulson et al 2012;Stevenson et al 2007).…”
Section: Tmod3 Associates With F-actin At Adherens Junctions and Contmentioning
confidence: 99%